A New Approach for the Synthesis of Highly Substituted Aromatic Rings: The Alkyne‐Mediated Approach. Issue 12 (11th February 2016) - Parsons, Philip J.; Jones, Daniel R.; Padgham, Alex C.; Allen, Lewis A. T.; Penkett, Clive S.; Green, Robert A.; White, Andrew J. P.
Abstract: Pentasubstituted aromatic rings serve as templates for drug design and can be conveniently prepared by the thermolysis of suitably substituted alkynes under microwave conditions. Abstract : Rings in the microwave ! Pentasubstituted aromatic rings serve as templates for drug design and can be conveniently prepared by the thermolysis of suitably substituted alkynes under microwave conditions.